2020
DOI: 10.1007/s13202-020-01006-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SO42−, Ca2+, and Mg2+ ions in Caspian Sea ion-engineered water on the rate of wettability alteration in carbonates

Abstract: Tuning the salinity and concentration of potential-determining ions, such as Mg2+, Ca2+, and SO42−, could alter the wettability toward a more water-wet state. The rate of alteration in carbonate rock wettability is a critical parameter to design the duration of the ion-engineered water flooding. Characteristic experiments, such as dynamic contact angle and pH measurements, ion chromatography, and spontaneous imbibition, are applied to study the rate of wettability alteration using different samples of ion-engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Academia and the industry experts have been using spontaneous imbibition, core flooding, atomic force microscopy, zeta potentiometry, and sessile drop contact angle measurements to study the effect of the ion-tuned water flooding. These studies can be grouped into two categories: macroscale and micro- to nanoscale. The former studies analyze the relationship between the injected and the produced fluids while the latter focus on nanoscale surface properties, though there have been several issues with upscaling the nanoscale surface properties …”
Section: Introductionmentioning
confidence: 99%
“…Academia and the industry experts have been using spontaneous imbibition, core flooding, atomic force microscopy, zeta potentiometry, and sessile drop contact angle measurements to study the effect of the ion-tuned water flooding. These studies can be grouped into two categories: macroscale and micro- to nanoscale. The former studies analyze the relationship between the injected and the produced fluids while the latter focus on nanoscale surface properties, though there have been several issues with upscaling the nanoscale surface properties …”
Section: Introductionmentioning
confidence: 99%
“…PDIs are primarily sulfate, calcium, and magnesium (SO 4 2− , Ca 2+ , Mg 2+ ) ions that interact with the carbonate surface. Hence, the amount of active ions in the injected brine and the porous media are essential for alteration in fluid/rock interactions and the LSW performance [21][22][23][24][25]. The concentrations of inactive ions, such as Na + and Cl − , are also critical in influencing different mechanisms [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…,Strand et al (2008),Romanuka et al (2012),Bazhanova and Pourafshary (2020), and others. They suggested that the MIE is the mechanism of the wettability alteration in the carbonate reservoirs.…”
mentioning
confidence: 99%